Construção de significado familiar diante da violação de túmulo - Motoyama, Érika Perina (2017)
Taking care of the dead destination is part of the human nature, being the grave a memory monument adopted by many families across several generations. Grave violation has been considered a crime in Brazil since 1851, thus, besides the material loss, there is also a symbolic offense. This phenomenon has been poorly studied by both psychology and other areas of science. The aim of this study was to learn about the construction of meaning attributed by the relatives facing grave violation. This is a multiple case study involving five residents of the metropolitan area in São Paulo, who went through semi-structured interviews and construction of genogram in order to map the members of the family buried in the graves. The data collected was assessed individually using thematic analysis technique and later discussed with integrated approach. In each case studied, particular issues were addressed, such as: grave as a material possession; violence in the cemetery space; emotional impact caused by grave violation; cemetery ambiguous role; loss of funeral customs; death taboo; grave as a place of affection and memories, banalisation of violation as a crime; appreciation of family tradition; grave as a place of memory and respect; cemetery as an irrelevant place; importance of the relationship during the life. This way, the links established, added to the cultural, religious and family aspects, have influence in the meaning conveyed to the grave and, consequently, in the relationship established with it. It was possible to identify that the time gap between the grave violation and the participation in the interview was not significant